A comparative study of tolerability and effects on immunoglobulin levels and CD19 cell counts with ocrelizumab vs low dose of rituximab in multiple sclerosis. Issue 4 (September 2020) - Evertsson, Björn; Hoyt, Tammy; Christensen, Angel; Nimer, Faiez AL; Foley, John; Piehl, Fredrik
Background: Rituximab (RTX) and ocrelizumab (OCR) are two anti-CD20 biologics used in MS; however, comparisons on safety and efficacy are rare. Objective: To compare treatment outcomes over the first year with RTX and OCR. Methods: Retrospective cohort study comprising MS patients initiating RTX at the Karolinska University Hospital (Sweden; n = 311) and OCR at Rocky Mountain MS Clinic (Utah, USA; n = 161), respectively. Results: Levels of immunoglobulin G measured in blood dropped 0.16 g/L (95% confidence interval 0.01 to 0.31) with each OCR infusion, but remained stable with RTX. In contrast, levels of immunoglobulin M decreased to a similar extent with both drugs. Ten and 15% of patients discontinued treatment with RTX and OCR, respectively (n.s), however, adverse events leading to treatment discontinuation were more common with OCR (6.8% vs 2.6%; p = 0.026). Only 3.1 and 1.6% discontinued OCR and RTX, respectively, due to lack of effect (n.s). The degree of B cell depletion was superior with OCR. Conclusion: Overall, differences between the two treatments were small. Although the study design precludes robust conclusions regarding the risk-benefit with the studied therapies, our findings indicate that the tolerability and safety with RTX is not inferior to OCR.